Assistance in Archives Management within the Ministry of Religion of Indragiri Hilir Regency - Komariah, Nur; Nursanti, Nursanti; Riska, Riska (Jurnal Masyarakat Mengabdi, 2024)
The difficulty of retrieving archives is one of the problems in archival management at the office of the Ministry of Religion of Indragiri Hilir district. Assistance with archives management at the Ministry of Religion office aims to ensure that all employees pay more attention to the correct management of archives, making it easier to find the documents needed, as well as being active in collecting data on incoming and outgoing letters. The method of assisting archives management is carried out by improving archives management, as well as creating a list of incoming and outgoing archives according to the type of archive. Through assistance with archival management and arranging archives regularly according to the established catalog. By improving archival management, the Abdimas team organizes room archives according to the specified catalog and provides services by helping employees find the documents they need. Through the program activity of archiving files by making regular lists of incoming and outgoing documents, the Abdimas team also makes a list of types of documents and the dates of the documents listed. Through archival management assistance activities, the number of archives is more neatly arranged according to the catalog, and the list of incoming and outgoing letters is neatly recorded, making it easier for employees and guests at the Ministry of Religion office to find the documents they need.